Evaluation of anti-diabetic effect and gall bladder function with 2-thio-5-thiomethyl substituted imidazoles as TGR5 receptor agonists. Issue 8 (15th April 2017) - Zhang, Xuqing; Sui, Zhihua; Kauffman, Jack; Hou, Cuifen; Chen, Cailin; Du, Fuyong; Kirchner, Thomas; Liang, Yin; Johnson, Dana; Murray, William V.; Demarest, Keith
Graphical abstract: A novel series of 2-thio-5-thiomethyl substituted imidazoles was discovered to be potent TGR5 agonists that possessed glucose-lowering effects while inhibiting gall bladder emptying in mice. Abstract: A novel series of 2-thio-5-thiomethyl substituted imidazoles was discovered to be potent TGR5 agonists that possessed glucose-lowering effects while inhibiting gall bladder emptying in mice.